Effects of Fuhe decoction on behaviors and monoamine neurotransmitters in different brain regions of CUMS combined with social isolation depression model rats - Ruoyun Zheng; Weifeng Xiong; Juan He; Xu Wang; Ranran Wang; Yu Hao (Journal of Traditional Chinese Medical Sciences, 2020)
Objective: To investigate the effect of Fuhe decoction on the behavior and levels of monoamine neurotransmitters in different brain regions in a depression rat model induced by chronic unpredictable mild stimulation (CUMS) combined with social isolation. Methods: Fifty male SD rats were randomly divided into a blank group, model group, fluoxetine group, Chaiqinwendan decoction group, and Fuhe decoction group. Chronic unpredictable mild stimulation combined with a social isolation method was used to replicate the depression rat model. After 42 days of administration, a tail suspension test and high-performance liquid electrochemical detection (HPLC-ECD) were used to detect the behavioral changes and changes in the content of monoamine neurotransmitters norepinephrine (NE), dopamine (DA), 5-hydroxytrytamine (5-HT), and metabolites in different brain regions of rats in each group before and after treatment. Results: Compared with the model group, the epinephrine (E) content in the Fuhe decoction group was highly significantly increased (P < .01). Compared with the model group, the 5-HT content of the prefrontal cortex in rats in the Fuhe decoction group was highly significantly increased (P < .01). Furthermore, compared with the model group, the 5-HT content in the hippocampus of rats in the Fuhe decoction group was significantly increased (P < .05). Conclusion: Fuhe decoction can improve the depression-like behaviors of model rats, and its antidepressant effect may be related to the increase in 5-HT content in the prefrontal cortex and hippocampus of rats.